Political Satire in Neo-Classical Age: John Dryden as an Example - Abdulameer Ketab, Athraa (Opción, 2019)
The current research deals with the political satire in the poems of Dryden “Absalom and Achitophel” and “The Medall”. In the poem “Absalom and Achitophel”, the poet selected a famous Biblical tale of Absalom who re- belled against his father David, at Achitophel’s evil initiation to ridicule and satirize the contemporary political state, while he filled the poem “The Medall” or “A Satire against Sedition” with generous criticism against the Whigs. The research consists of three sections. The first section addresses the introduction and the second one discusses the Political Satire in “Absa- lom and Achitophel”, while the third one covers “The Medall”. The research ends up with a conclusion, endnotes and a list of references.